Formation and determination of the oxidation products of 5-methylcytosine in RNA. Issue 8 (20th May 2016) - Huang, Wei; Lan, Meng-Dan; Qi, Chu-Bo; Zheng, Shu-Jian; Wei, Shao-Zhong; Yuan, Bi-Feng; Feng, Yu-Qi
Abstract : Chemical labeling coupled with LC-MS enables the sensitive and simultaneous detection of the oxidative products of 5-methylcytosine. With this method, we can determine 5-methylcytosine, 5-hydroxymethylcytosine, 5-formylcytosine and 5-carboxylcytosine in RNA of mammals. Abstract : Similar to the reversible epigenetic modifications on DNA, dynamic RNA modifications were recently considered to constitute another realm for biological regulation in the form of "RNA epigenetics". 5-Methylcytosine (5-mC) has long been known to be present in RNA from all three kingdoms of life. However, the functions of 5-mC in RNA have not been fully understood, especially for the RNA demethylation mechanism. The discovery of 5-hydroxymethylcytosine (5-hmC) in RNA together with our recently reported 5-formylcytosine (5-foC) in RNA indicated that 5-mC in RNA may undergo the same cytosine oxidation demethylation pathway with generating intermediates 5-hmC, 5-foC, and 5-carboxylcytosine (5-caC) by ten–eleven translocation (Tet) proteins as that in DNA. However, endogenous 5-caC in RNA has not been observed so far. In the current study, we established a method using chemical labeling coupled with liquid chromatography-mass spectrometry analysis for the sensitive and simultaneous determination of the oxidative products of 5-mC. Our results demonstrated that the detection sensitivities of 5-mC, 5-hmC, 5-foC and 5-caC in RNA increased by 70–313 folds upon 2-bromo-1-(4-diethylaminophenyl)-ethanone (BDEPE) labeling. Using this method, we discovered the existence of 5-caC in the RNA of mammals. In addition, we found the 5-mC occurs in all RNA species including mRNA, 28S rRNA, 18S rRNA and small RNA (<200 nt). However, 5-hmC, 5-foC and 5-caC mainly occur in mRNA, and barely detected in other types of RNA. Furthermore, we found that the content of 5-hmC in the RNA of human colorectal carcinoma (CRC) and hepatocellular carcinoma (HCC) tissues significantly decreased compared to tumor adjacent normal tissues, suggesting that 5-hmC in RNA may play certain functional roles in the regulation of cancer development and formation.